The Environmental Multi-Sector DSGE model EMuSe: A technical documentation - Natascha Hinterlang; Anika Martin; Oke Röhe; Nikolai Stähler; Johannes Strobel (Deutsche Bundesbank, 2023)
Climate change and climate policy will have far-reaching economic implications, thereby also posing new challenges for macroeconomic analysis. This is partly because climate risks have an important global dimension. Moreover, climate change and climate polices are likely to affect different economic sectors to varying degrees. Hence, in order to adequately gauge the macroeconomic implications of climate risks, models with sufficient regional and sectoral differentiation are needed. Against this background, we developed the environmental multi-sector dynamic stochastic general equilibrium model EMuSe. This paper presents the main features of the benchmark closed-economy flexible-price model, an open-economy extension of the model, a variant of the model with price-setting frictions and selected applications to illustrate key transmission channels. In order to give those who are interested the opportunity to gain more experience with EMuSe, the model codes are published together with this documentation.
Keywords: E3; E6; F4; H3; Q5; 330; climate risks; DSGE; production linkages; sectoral heterogeneity